Pengaruh Audit Internal, Pengendalian Internal, Kualitas Audit, Good Corporate Governance, Terhadap Pencegahan Kecurangan (Fraud) Pada Bank Bca Area Medan - Wulandari, Bayu; Glenardy, Glenardy; Romi, Michael; Ricky, Ricky (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
This research intended to test whetherIInternal Audit,IInternal Control,I Audit’s Quality,IGood    CorporateIGovernanceIhaveIInfluenceIto Fraud Prevention.IthisIis theI research I conducted       on I banking company I, which is BCA bankI with a population I research I more than I 180 I             (one hundred and eighty)Iaudit employees who worked in IBCA Ibank in IMedan. After             carrying out various considerations, this research took a sample of 80 people from various             audit divisions. The method which is used in this research I is theI-analysis of the multiple      linear regression method. The dependent variable I is Fraud Prevention, while the             independent variables I are Internal Audit, Internal Control, Audit’s Quality, I and Good       Corporate Governance. The results of this research show that the majority of the Audit’s        QualityI has a significant positive effect on fraud prevention measures, while I for Internal   Audit, Internal Control I, and Good Corporate Governance do not have the influence of fraud             prevention.